PENGEMBANGAN BORDIR KHAS ACEH DALAM BIDANG KEDOKTERAN GIGI - Diana Setya Ningsih; Dewi Saputri; M Ridha Siregar (Dentistry Faculty, 2018)
Aceh embroidery is identical with Acehnese motifs that are embroidered manually. This craft is generally used as a souvenir that is implemented in fabrics, bags, wallets, regional clothes and so on. Aceh embroidery innovation has reached the stage of meeting market demand, however, there has been no innovation that leads to the field of dentistry. Therefore, this service aims to develop Acehnese embroidery in the field of dentistry. The method used is training and mentoring methods and strives for effective marketing for partners. The results obtained from this service are partners able to become independent and able to improve their economic level. The results of dedication that have been produced are fabric, Muslim women's prayer dresses, clothes, and veil that have been modified between Acehnese embroidery and dental elements.Keywords: Embroidery, teeth, Aceh, innovation, crafts, dentistry